The Effects of Low FODMAP Diet on the Quality of Life and Gastrointestinal Symptoms in Children with Irritable Bowel Syndrome. A Pilot Study - Ecem Ipek Altınok; Çiğdem Ömür Ecevit; Zeynep Akışın; Aslı Ata Teneler; Özlem Bağ (Galenos Publishing House, 2021)
Objective: Irritable bowel syndrome is a disease that negatively affects life. Recently, diet therapies have been emphasized. Our study, the aim was to investigate the effect of low FODMAP (fermented oligo-, di-, monosaccharide and polyols) diet on the frequency of gastrointestinal symptoms and the effects on quality of life in patients with IBS. Method: 18 children aged between 7-18 years, who were diagnosed with IBS, followed by University of Health Sciences Izmir Dr. Behçet Uz Children's Diseases and Surgery Training and Research Hospital the Child Gastroenterology, Hepatology and Nutrition Clinic were included in the study. The appropriate KINDL scale was applied at the time of application and 2 weeks after the end of the low FODMAP diet. GIS symptoms of the week 0 and 6 KINDL results were compared. KINDL scale was applied to the families before and after dieting and the results were compared. Results: The study was completed with 10 patients. The most common symptom was abdominal pain and it was present in all patients. All symptoms were found to decrease after diet but it was not significant. There was a significant increases in emotional well-being, family divisions and total KINDL results at the 6th week of diet in the children In parent KINDL scales, the results were not considered significant. Conclusion: Despite there was a decrease in GIS related complaints and increase in quality of life in IBS patients who underwent low FODMAP diet, it has been found appropriate to continue the study with larger patient groups for longer follow-up periods.